Research on Geographical Education in Vietnam Journals Within The 10-Year Period (2010 - 2019) - Thang, Ha Van; Thong, Le Duy; Thanh, Ta Chi (Universitas Negeri Semarang, 2021)
Geographical education is a term that is not commonly used in research on Educational Science in Vietnam. Instead, researchers often refer to concepts such as Geography teaching or Geography lecturing. Geographical education is defined as the amalgam of two academic fields: Geography and Education (Gerber, 1996). Studies of geographical education published in journals over the past 10 years reflect the development of this field in my country. The objective of this study is to give an outline of research on geographical education in Vietnam between 2010 and 2019. The search for research articles uses Grounded Theory and is carried out in three phases. This research has contributed to the establishment of the geographical education definition in order to form a conceptual framework for the studies on the same field in Vietnam. More importantly, it generalizes prominent trends in the research on geographical education during the 10-year period as a basis for research strategy planning for the following phases. These results play an important role in improving education strategy in Vietnam from 2018.